If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-63=2x+9-19
We move all terms to the left:
-63-(2x+9-19)=0
We add all the numbers together, and all the variables
-(2x-10)-63=0
We get rid of parentheses
-2x+10-63=0
We add all the numbers together, and all the variables
-2x-53=0
We move all terms containing x to the left, all other terms to the right
-2x=53
x=53/-2
x=-26+1/2
| -p-3p=-6p+8 | | -3(u+2)=-4(2u-3)+9u | | 7(x-5)=6(x+5) | | 1x+1.5x=3275 | | 4(x-3)-3x+1=-13x | | 3c+5-8c=17 | | 150-x=237 | | 20+6b=44 | | 5x+20/x=11 | | 2x+8+x+2=180 | | y-(9/10)y=12 | | -9+t=7 | | 2x+37=4x+3 | | 7+3h=1-5 | | -u+241=107 | | X2+(16.667x)2=324 | | -1+a=7 | | (6x+7)+(13x+21=180 | | -1+a=6 | | 4(x+9)=6x-4 | | 3-20=-7=w | | 6x-53=4x+7 | | -3(9x+2)-6x=3(x-5)-1 | | 6=w4 | | c-67=85 | | 3(2x+6)=-32+14 | | 5x+20/x=10 | | 6=-3+2x | | 2(4x+6)=-16+20 | | (2b=5)=9 | | 12x+5=3-13x+13 | | -3.4h=30.6 |